Queer criminology as activism - Ball, Matthew (Critical criminology, 2016)
Belknap’s recent call for greater criminological activism in the service of social justice identifies queer criminology as an important site for such activism. Indeed, much of the work undertaken by queer criminologists is already motivated by a concern to address a variety of injustices - whether in the form of discrimination, heteronormativity, gender binarism, or invisibility - experienced by queer communities in the realm of criminal ustice, criminology, and beyond. In this paper, I explore the existing and possible future connections between queer criminology and activism. I highlight the ways in which queer politics have always involved social activism, including activism relating to criminal justice issues. I then suggest some possible directions for expanding queer criminological activism within the traditional academic roles of research, teaching, and service. Pursuing such directions, I argue, is necessary in order to set the foundation for further queer criminological activism beyond academia.